THE EFFECT OF SOCIO-ECONOMIC ON SOCIAL CAPITAL IN INDONESIA - Ratni Heliati; Tio Riyono (TRIKONOMIKA, 2018)
The current world development agenda led to a focus called the 2030 Sustainable Development Goals (SDGs). There were 17 development goals that became the world’s commitment to be achieved soon. The results of the consensus in 1995 at the World Summit for Social Development stated that the development must make humans as the center of development. One of the benchmarks for human development was based on the Social Capital index. Various countries had developed the concept of social capital. So far, the capital of the OECD had become the most referenced, such as Canada, Australia and the United Kingdom, as a reference in developing indicators of social capital. This study aimed to prove Lin’s theory which stated that assets or economics were directly proportional to the development of social capital. The results showed that economic variables such as GRDP per capita were inversely proportional to social capital. Subsequently social capital was significantly influenced negatively by Indonesia’s democracy index and significantly influenced positively by population density